2023
DOI: 10.5500/wjt.v13.i1.10
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of total pancreatectomy with islet autotransplantation: A systematic review and meta-analysis

Abstract: BACKGROUND Despite the increased use of total pancreatectomy with islet autotransplantation (TPIAT), systematic evidence of its outcomes remains limited. AIM To evaluate the outcomes of TPIAT. METHODS We searched PubMed, EMBASE, and Cochrane databases from inception through March 2019 for studies on TPIAT outcomes. Data were extracted and analyzed using comprehensive meta-analysis software. The random-effects model was used for all variables.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…As illustrated in Table 2, case series have shown that TP decreases the amount of pain that the patients experience 2,19‐24 . Additionally, in a meta‐analysis by Khazaaleh et al, 21 studies from 1980 to 2017 including 1011 patients revealed that narcotic independence was achieved in 53.5% of adults after TPIAT 25 . The degree of narcotic independence and the time it takes for patients to reduce their narcotic usage tends to be specific to each patient.…”
Section: Outcomes After Tpiatmentioning
confidence: 99%
See 1 more Smart Citation
“…As illustrated in Table 2, case series have shown that TP decreases the amount of pain that the patients experience 2,19‐24 . Additionally, in a meta‐analysis by Khazaaleh et al, 21 studies from 1980 to 2017 including 1011 patients revealed that narcotic independence was achieved in 53.5% of adults after TPIAT 25 . The degree of narcotic independence and the time it takes for patients to reduce their narcotic usage tends to be specific to each patient.…”
Section: Outcomes After Tpiatmentioning
confidence: 99%
“…2,[19][20][21][22][23][24] Additionally, in a metaanalysis by Khazaaleh et al, 21 studies from 1980 to 2017 including 1011 patients revealed that narcotic independence was achieved in 53.5% of adults after TPIAT. 25 The degree of narcotic independence and the time it takes for patients to reduce their narcotic usage tends to be specific to each patient. However, reduction in narcotic usage after TPIAT has been associated with increased postoperative narcotic use, previous pancreatic stent placement, early sphincterotomy, and a high number of previous stents.…”
Section: Outcomes After Tpiatmentioning
confidence: 99%
“…It showed that 31.8% of adult patients and 47.7 children patients were insulin-independent after TPIAP. 104 As for the quality of life, Takaki et al from Japan evaluated the efficacy of TPIAP among five patients with CP followed-up for 12 months and found a significant improvement in quality of life among these patients. 105 …”
Section: Surgical Strategymentioning
confidence: 99%